Design and Analysis of Experiments : Volume 3 : Special Designs and Applications - Hinkelmann, Klaus, 1932- (Hoboken, NJ : Wiley-Interscience, 2012)
This book discusses special modifications and extensions of designs that arise in certain fields of application such as genetics, bioinformatics, agriculture, medicine, manufacturing, marketing, etc. Well-known and highly-regarded contributors have written individual chapters that have been extensively reviewed by the Editor to ensure that each individual contribution relates to material found in Volumes 1 and 2 of this book series. The chapters in Volume 3 have an introductory/historical component and proceed to a more advanced technical level to discuss the latest results and future development.
4.5.2 GLMs with Group Effects.
Includes bibliographical references and indexes.
Keywords: Experimental design; Mathematical statistics; Computational fluid dynamics; Heat -- Transmission; Mathematics; Science; Physics; Reference & resource series; TECHNOLOGY & ENGINEERING -- Hydraulics; Mathematical statistics; Experimental design; Electronic books; Electronic books